KEPALA NEGARA DALAM SISTEM KETATANEGARAAN INDONESIA PERSPEKTIF SIYASAH ISLAM - Septiana Rizco Nurfaizi (DIKTUM: Jurnal Syariah dan Hukum, 2020)
In the Indonesian constitutional system, the Head of State is held by a president this refers because in Indonesia the country uses a democratic and presidential system. Where presidential is known by using the Trias Politica system in which power is divided into three parts (Legislative, executive and judiciary). To appoint a head of state who manages a country and takes care of his problems, the condition of a candidate for head of state is a very important issue in determining a nation, it becomes one of the needs that must exist at all times. Unlike the parliamentary system, where the head of state can have two heads of state, namely the president and prime minister, but this presidential only has one head of state, namely only one president, democracy is a system of government which is organized by the people, by the people and for the people, therefore, for the president to do it through elections where the people determine. and the president only has a position for 5 years and 2 periods to lead, this is done to minimize power that is too long, while the elected head of state must be able to hold the mandate of the people in accordance with what is written in Islamic law, the head of the state must be honest and trustworthy and can be an example for his people because whatever the decision of the head of the state the people must obey.